Analysis Of Factors Affecting Audit Delay - Dian Efriyenty (Jurnal Riset AKuntansi dan Bisnis, 2021)
ABSTRACTThe current phenomenon is that the Financial Services Authority still accepts delays in financial reporting carried out by several companies. The presence of delays in information submission of financial reports due to audit delay causes a decrease in the level of investor confidence, this can affect the selling price of shares in the capital market. This study aims to examine audit opinion, company size and size of public accounting firm (KAP) on audit delay. The sample of this research is manufacturing companies. The results showed that the audit opinion has no negative but not significant effect on audit delay, company size has a negative but significant effect on audit delay, KAP size has no negative but not significant effect on audit delay. The F test results show that the audit opinion variable, firm size and the size of KAP obtained an Fcount of 3.469 and an Ftable of 2.87 along with a significance value of 0.026. These results prove that the Fcount value is greater than the Ftable value (3.469 2.76) and the significance value is smaller than the ? = 0.05 (0.026 0.05).